A new Panamanian species of Miconia (Melastomataceae: Miconieae) - Almeda, Frank; Pacifico, Ricardo (Phytotaxa, 2025)
Miconia sparsiflora is described as a new species known only from lower montane tropical forests on the Caribbean slopes of Panama. A line drawing, a distribution map, a recommended conservation assessment, and comparisons with presumed closest relatives based on morphology are provided. This species is readily recognized by its copious mixture of smooth spreading black trichomes and ground layer of brown amorphous branlike indumentum on cauline internodes, leaves with ciliate-denticulate margins, rounded bases, and an abaxial indumentum consisting of spreading smooth trichomes 0.5–2 mm long on and between elevated veins and also randomly covered with minute amorphous branlike trichomes and glistening resinous-granulose trichomes on and between the elevated primary, secondary, and higher order veins. Other distinctive features include its few-flowered racemiform inflorescence with flowers that are nodding in bud, stamens that are alternately somewhat unequal in length, and seeds with a bluntly tuberculate testa. The new species is compared with the widespread M. gracilis and two species of northwestern South America, M. subspicata, and M. tenensis.